If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 144 = -13(x + 5) Reorder the terms: 144 = -13(5 + x) 144 = (5 * -13 + x * -13) 144 = (-65 + -13x) Solving 144 = -65 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 144 + 13x = -65 + -13x + 13x Combine like terms: -13x + 13x = 0 144 + 13x = -65 + 0 144 + 13x = -65 Add '-144' to each side of the equation. 144 + -144 + 13x = -65 + -144 Combine like terms: 144 + -144 = 0 0 + 13x = -65 + -144 13x = -65 + -144 Combine like terms: -65 + -144 = -209 13x = -209 Divide each side by '13'. x = -16.07692308 Simplifying x = -16.07692308
| 0=6-6x | | 4x^4+36x^2=0 | | 9x-3=-2x-18 | | 7(4x+9)=6(11x-12) | | 7x(4x+9)=6(11x-12) | | -106-10x=9x+20 | | 3p+6m=3m-9 | | 8x-9y=-16 | | 9x-6=10x+12 | | 9(x+2)+6(x+6)=6x-6 | | 71.80=25+0.15 | | 4y+3y=11 | | -x-3y=-23 | | x+4-3x^2=0 | | 3-2x+x=5x-5+2x | | 8w-32=4w | | -7-x=3x+17 | | 2x^2-50=24 | | 1x-4+1x=5(9-4x) | | 2-8x+1(x-4)=2(x-7) | | 6x+3=2x+31 | | m-14.6=9.74 | | 4+2x=5x-2 | | w-8=32 | | 4y-8=5y-1 | | 17dl=l | | 3x+4=-36-5x | | x=2*8+77 | | 16+5x= | | 3x+4=-35-5x | | (2x+5)x(7x-2)=(4x+3)x(5x-1)+82 | | 4(d-7)=524 |